Pengembangan Keunggulan Bersaing UMKM Sektor Fashion di Kota Denpasar Berbasis Digitalisasi dan Kapabilitas Inovasi: Peran Mediasi Organizational Agility - Rahmayanti, Putu Laksmita Dewi; Pratiwi, Komang Ary (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
MSMEs in the local fashion sector must be able to have a competitive advantage compared to competitors. The maintenance of a competitive edge is important for micro, small, and medium enterprises (MSMEs) operating within the fashion sector, as it enables them to surpass their competitors through the production of higher or more cost-effective products and services. This, in turn, leads to heightened sales performance. The integration of innovation, digitization, and organizational agility capabilities is crucial for the development of this model in order to attain a competitive edge. Historically, the integration of digitalization, innovation capabilities, and organizational agility within the competitive advantage framework for MSMEs was infrequently implemented. The purpose of this study is to test and explain the development of competitive advantage for MSMEs in the fashion sector in Denpasar City based on digitalization and innovation capabilities mediated by organizational agility. Based on the results of the study, it was found that innovation and digitalization capabilities have a positive and significant effect on organizational agility and competitive advantage. The implications of this research are that in order to have a competitive advantage, MSMEs in the fashion sector in Denpasar City must have good organizational agility, innovation capability, and digitalization.